Psychiatric disorders in multiple sclerosis patients Transtornos psiquiátricos em pacientes com esclerose múltipla - Mirella Martins Fazzito; Sérgio Semeraro Jordy; Charles Peter Tilbery (Arquivos de Neuro-Psiquiatria)
Multiple sclerosis (MS) is a demyelinating disease showing variable clinical presentation. Optic neuritis is the most common symptom, followed by motor and sensitive manifestations. It is known that this disease may be related to several psychiatric disorders, especially depression. In this study we will discribe 5 cases of MS patients harboring psychiatric disorder related or unchained by the disease itself. Esclerose múltipla é uma doença desmielinizante com variadas apresentações clínicas. Neurite óptica e manifestações motoras e sensitivas são as mais frequentemente observadas. É conhecido que a doença pode ser associada a vários transtornos psiquiátricos, sobretudo depressão. Neste estudo são descritos 5 casos de pacientes com esclerose múltipla com transtornos psiquiátricos relacionados ou associados a própria patologia.